(untitled) (Plant Tissue Culture and Biotechnology, 2008)
A regeneration protocol ensuring a high frequency rooting of micro-shoots derived from apical and axillary buds of suckers of banana cv. Sagar was achieved by using liquid medium. When the explants were cultured on MS medium supplemented with 0.5 mg/l each of BA, Kn and NAA, a large number of shoots developed. With the progression of the number of subcultures, shoot proliferation was enhanced. Addition of 10 % coconut water to the medium increased the number of shoots per culture and growth of individual shoots. Shoots rooted well within two weeks, when they were separated individually and sub-cultured in 1.0 mg/l IBA supplemented half strength MS liquid and agar-gelled medium but rooting percentage and their growth were superior in the liquid medium to agar-gelled medium. Rooted plantlets were transferred to small polythene bags containing sterile sand, soil and humus (1 : 2 : 1) and maintained with a high humidity for acclimation. Acclimation and transplantation performances were found to be superior in plants that were rooted in the liquid medium. Key words: Banana, Liquid medium, Regeneration, Acclimation, Transplantation DOI = 10.3329/ptcb.v16i1.1100 Plant Tissue Cult. & Biotech. 16(1): 11-18, 2006 (June)